DEGREE OF ACIDITY (pH) OF SALIVA WITH DENTAL CARIES AT SDN KAYEE LEUE, ACEH BESAR DISTRICT - Elfi Zahara; Niakurniawati Niakurniawati; Mufizarni Mufizarni (JDHT Journal of Dental Hygiene and Therapy, 2023)
Dental caries can be caused by various factors, one of which is the presence of saliva or saliva that always wets the teeth so that it can affect the oral environment. This study aims to determine the relationship between salivary pH and dental caries in students at SDN Kayee Leue, Want Jaya District, Aceh Besar District. The research method is analytic with a cross-sectional or cross-sectional design, which is to determine the relationship (pH) of saliva with dental caries. This research was conducted at SDN Kayee Leue Aceh Besar on April 13 to May 20, 2022 with a population of 70 students in grades IVa and IVb and the sample used was total sampling. Based on the results of the study, 70 students who had acidic salivary pH with dental caries were 36 students (51.4%), students who had a neutral salivary pH with dental caries were 32 students (45.7%) and students with alkaline salivary pH with dental caries as many as 2 students (2.9%). The conclusion of the statistical test results with a value of p = 0.000 < 0.05, namely there is a significant relationship between (pH) saliva and dental caries in students of SDN Kayee Leue, Sub-District of Want Jaya Aceh Besar, it is recommended to students to increase awareness in maintenance and diligent brushing teeth twice a day, in the morning after eating and at night before going to bed.